Factor Analysis of Semen Quality in Chicken and Its Impact on Fertility - Yunlei Li; Yanyan Sun; Aixin Ni; Hailai Hagos Tesfay; Adamu Mani Isa; Yunhe Zong; Hui Ma; Jingwei Yuan; Jilan Chen (Animals)
Evaluation of semen quality is crucial for predicting fertility success in artificial insemination and eventual rooster selection within poultry breeding programs. However, the multitude of parameters obtained in semen quality analysis makes it challenging for breeders to make informed selection decisions. This study evaluated semen samples from 210 roosters in seven chicken breeds, using a computer-aided sperm analysis (CASA) system. A multivariate approach utilizing factor analysis (FA) was applied to simplify the data. The FA condensed 14 semen quality traits into 3 factors, linearity factor, velocity factor, and quantitative factor, explaining 75.82% of the original variations. The Beijing-You breed was selected to analyze the association between fertility and these semen quality factors, and we found high correlation between fertility and quantitative (r = 0.84) and linearity (r = 0.63) factors, and low correlation with the velocity factor (r = 0.19). Based on individual factor scores, breed clustering revealed distinct profiles with Houdan, Tibetan, and White Leghorn demonstrating lower sperm counts and poor linearity. Columbian Plymouth Rock exhibited high speed with poor linearity while Beijing-You, Rhode Island Red, and Barred Plymouth Rock displayed higher sperm counts with compromised speed and linearity. This study demonstrates that FA effectively consolidates multiple semen quality traits into fewer, biologically relevant factors. These findings provide valuable insights into breed-specific reproductive characteristics and offer actionable information for optimizing breeding in poultry production.